Sources of fashion inspiration - Sunanda
nspiration has an important place in the fashion design process. In a fashionable way, the qualities that the designer is influenced by is the research result for his inspiration. The design elements and principles help in interpretation of the design to convey the design details in the mind of the designer onto paper or fabric. This is important for the fashion designer to utilise art as a source of inspiration. A number of sources of inspiration and information, in addition to books on costume history, are invaluable to the fashion designer and the historian of fashion. They include predictions of style and market trends, visual sources of creative inspiration, and a variety of forms of historical evidence. Sources of information on style and market trends include forecasting services, trade magazines, newspapers, advertising material, and fashion magazines. Sources from which the designer can draw inspiration include paintings and visual imagery from the theatre, cinema, and popular culture. Historical evidence includes portrait paintings, fashion plates and magazines, photographs, literary sources, pattern books, and trade catalogues.